2022
DOI: 10.33988/auvfd.855124
|View full text |Cite
|
Sign up to set email alerts
|

Molecular, biochemical, and histopathological effects of long-term low and high-percentage fructose consumption on the liver in rats

Abstract: The aim of this study was to investigate the lipogenic and inflammatory effects of low and high percentage fructose solutions in rats. Wistar albino rats were fed with fructose solutions for 10 weeks. Groups were as follows: Cont (Control), F15 2 (Fructose 15%), F30 (Fructose 30%), F60 (Fructose 60%). Body weights of rats were weekly measured. Also, lipogenic and inflammatory genes expression levels, biochemical parameters and histopathological changes in liver were investigated. After 10 weeks, it was observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…In the group in which ASA and Vit. C were given combined treatment, fatty liver was found to be statistically reduced (p<0.05).Histopathological results of applied F30 were similar to those of other studies(60,61). When the histopathological results of pancreas were evaluated; statistically significant (p<0.05) changes were detected in the F group compared to the control group, such as an increase in the diameter of the intralobular canal, an increase in fat tissue in the exocrine region and congestion and proliferation in the vessels in the connective tissue.Van Geenen et al suggested that interlobular and total pancreatic steatosis is associated with NAFLD, and that total pancreatic steatosis is a statistically significant predictor for the presence of hepatic steatosis(62).…”
supporting
confidence: 87%
See 1 more Smart Citation
“…In the group in which ASA and Vit. C were given combined treatment, fatty liver was found to be statistically reduced (p<0.05).Histopathological results of applied F30 were similar to those of other studies(60,61). When the histopathological results of pancreas were evaluated; statistically significant (p<0.05) changes were detected in the F group compared to the control group, such as an increase in the diameter of the intralobular canal, an increase in fat tissue in the exocrine region and congestion and proliferation in the vessels in the connective tissue.Van Geenen et al suggested that interlobular and total pancreatic steatosis is associated with NAFLD, and that total pancreatic steatosis is a statistically significant predictor for the presence of hepatic steatosis(62).…”
supporting
confidence: 87%
“…The main function of ascorbic acid as an antioxidant is to prevent the formation of lipid hydroperoxides (20) Increased TNF-α expression triggers triglyceride production and leads to liver steatosis (59). It has been shown that fructose at a concentration of 30% and above can upregulate TNF-α expression, which is reflected in histopathological findings (60).…”
Section: Discussionmentioning
confidence: 99%
“…While the relations between biochemical parameters were as expected, notable correlations were determined between proteins and biochemical parameters. SREBP‐1c and PPARγ are both transcription factors that play crucial roles in lipid metabolism (Özkan et al, 2022; Özkan & Yakan, 2019). In mammals, upregulation of SREBP‐1c leads to increased expression of genes involved in lipogenesis, such as PPARγ.…”
Section: Discussionmentioning
confidence: 99%